PENGEMBANGAN MEDIA AUGMENTED REALITY BERBASIS ASSEMBLR EDU UNTUK MENINGKATKAN KARAKTER PEDULI LINGKUNGAN SISWA KELAS IV SD GMIT KUANINO 3 - Gracela Natalia Hendrik; Yulsy Marselina Nitte; Roswita Lioba Nahak (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Assemblr Edu-based Augmented Reality learning media to increase environmental awareness plays a very important role in the learning process. This is intended to help students understand the material to be learned through learning media. The purpose of this study is to determine the feasibility, attractiveness, practicality, and effectiveness of Assemblr Edu-based Augmented Reality learning media in improving the environmental awareness of fourth-grade students at SD GMIT Kuanino 3. This research is a research and development (R&D) study using the ADDIE model, which consists of five stages, namely analysis, design, development, implementation, and evaluation. The instruments used in this study were subject matter expert questionnaires, language expert questionnaires, and media expert questionnaires. Based on the research, the results of the subject matter expert validation were 88.75% with a very feasible criterion, the language expert validation was 92.5% with a very feasible criterion, and the media expert validation was 81.25% with a very feasible criterion. The hypothesis test results obtained a significant value of 0.000<0.05, which indicates a difference between H0 and Ha accepted, with a teacher response of 96.25% with a very good criterion and a student response of 93.18% with a very good criterion. Overall, this learning media received a very good response from teachers and students, supported by an improvement in student learning outcomes through an average (N-gain) of 0.7748>0.7, which is a high category. Therefore, the Assemblr Edu-based Augmented Reality learning media for improving environmental awareness is suitable for use as a learning medium.